Analisis Hadits Tentang Keharusan Pemimpin Dari Bani Quraisy - Jaya, Canra Krisna; Lubis, Rahmat Kurnia (Al Ashriyyah, 2021)
This article aims to explain how to understand the hadith about the leadership of the Banu Quraysh. This study uses descriptive analysis method, with a qualitative approach. This article concludes, First, textually there is no debate about the hadith of the Bani Quraysh leadership and Islamic thinkers accept this. Second, the Banu Quraysh became a sunatullah rule, becoming a leader in global coverage, but not regionally. Third, leadership in the regional scope provides opportunities for leaders who come from non-Bani Quraysh to occupy leadership positions. Fourth, the opportunity to become a leader for the non-Ban Quraysh must still pay attention to the criteria or conditions for becoming a leader. Starting from who chooses then who will be chosen.